Econnoitering Data Protection and Recovery Strategies in the Cyber Environment: A Thematic Analysis - Muhammad Ibrar; Samavia Riaz; Younus Khan; Ayyan Asif; Khalid Hamid; Muhammad Waseem Iqbal; Muhammad Asim (International Journal for Electronic Crime Investigation, 2024)
This paper discusses the performance and reliability of different strategies for database backup and recovery within a controlled environment, focusing on the comparison between full, incremental, and transaction log backups. Experimentation based on these strategies is designed to assess the effectiveness in terms of the capability to handle data loss scenarios such as accidental deletion, system crashes, and hardware failure. A sample database environment is established on MySQL, PostgreSQL, or SQL Server. The metrics recorded in the baseline state include response time, data throughput, and resource utilization. The research considers various recovery models, including Simple, Full, and Bulk-Logged recovery, in comparison with the chosen backup strategies. The influence of each strategy on data protection, recovery time, and usage of system resources is considered. The findings of the survey are derived with reference to the perception of IT professionals and database administrators to ascertain which of the full backups and full recovery models they favor most, as they consider it by storage capacity and system performance factors. The output will be beneficial to businesses interested in optimizing their strategies for backups and recovery within specified data protection and performance considerations.